2007
DOI: 10.1126/science.1142448
|View full text |Cite
|
Sign up to set email alerts
|

Queen Pheromone Blocks Aversive Learning in Young Worker Bees

Abstract: Queen mandibular pheromone (QMP) has profound effects on dopamine signaling in the brain of young worker honey bees. As dopamine in insects has been strongly implicated in aversive learning, we examined QMP's impact on associative olfactory learning in bees. We found that QMP blocks aversive learning in young workers, but leaves appetitive learning intact. We postulate that QMP's effects on aversive learning enhance the likelihood that young workers remain in close contact with their queen by preventing them f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 18 publications
(7 reference statements)
3
112
0
Order By: Relevance
“…(3) Exposure to a recently extinction-trained familiar mouse results in inhibition of extinction learning, an effect not mediated by an olfactory chemosignal emitted from a recently extinguished familiar mouse or by b-PEA. Similar to the ability of queen pheromone to impair aversive learning without modifying appetitive learning in adult bees (Vergoz et al 2007) and to context-specific olfactory steroid chemosignal regulation of mood in humans (Jacob and McClintock 2000), our data that suggest fear-or stressrelated social signals emitted by mice may influence associative learning depending on the valence of the task.…”
Section: Discussionmentioning
confidence: 81%
“…(3) Exposure to a recently extinction-trained familiar mouse results in inhibition of extinction learning, an effect not mediated by an olfactory chemosignal emitted from a recently extinguished familiar mouse or by b-PEA. Similar to the ability of queen pheromone to impair aversive learning without modifying appetitive learning in adult bees (Vergoz et al 2007) and to context-specific olfactory steroid chemosignal regulation of mood in humans (Jacob and McClintock 2000), our data that suggest fear-or stressrelated social signals emitted by mice may influence associative learning depending on the valence of the task.…”
Section: Discussionmentioning
confidence: 81%
“…Levels of Amdop3 expression in the antennae decrease rapidly during the first week of adult life perhaps contributing to the well-documented decline in responsiveness to QMP with age. Vergoz et al (2007b) found that bees exposed to QMP for 4 to 6 days from the time of adult emergence were not able to associate an odour with an aversive stimulus suggesting that their ability to predict punishment was blocked. Interestingly, bees treated in the same way retained their ability to form appetitive olfactory memories.…”
Section: Qmp Affects Da Signalling In the Beementioning
confidence: 99%
“…One possible benefit to the queen of being able to block aversive learning in the young workers is that they will not associate the queen with any unpleasant effects of high concentrations of her pheromone. In contrast to young bees, bees of foraging age appear to be repelled by QMP (Vergoz et al 2007b), and potentially also by nurses (see Fan et al 2010) and perhaps even the queen herself. Fan and colleagues have recently shown that QMP exposure alters patterns of cuticular hydrocarbons in worker bees (Fan et al 2010) and that nurses and foragers differ in their cuticular hydrocarbon profiles, probably because they are exposed to different levels of QMP.…”
Section: Qmp Affects Da Signalling In the Beementioning
confidence: 99%
“…Pheromones are a class of environmental cues that are known to exert profound effects in insect brains (Grozinger et al, 2003Alaux and Robinson, 2007;Beggs et al, 2007;Grozinger and Robinson, 2007;Vergoz et al, 2007). In mice, odors from soiled bedding of dominant males have been shown to stimulate neurogenesis in the olfactory bulb and the hippocampus of adult females (Mak et al, 2007).…”
Section: Introductionmentioning
confidence: 99%